Trends in diagnostic nuclear medicine in Sweden (2008–2023): utilisation, radiation dose, and methodological insights - Anja Almén (EJNMMI Physics)
Abstract Background Diagnostic imaging is a dynamic medical field. In nuclear medicine, advancements introduce new procedures utilising innovative radiopharmaceuticals. These developments may influence supply requirements and exposure levels for the patient population. Surveying the frequency of procedures, types of pharmaceuticals, and administered activities provides valuable insights into utilisation trends and radionuclide demand. This knowledge also guides the prioritisation of radiation protection efforts at national and local levels. In Europe, radiation dose assessments for medical exposures are mandatory according to the directive´s requirements. Methods This study evaluated the utilisation of diagnostic nuclear medicine procedures in Sweden over 15 years (2008–2023), focusing on procedure frequency, effective dose, and collective effective dose. Comprehensive data from all Swedish clinics performing nuclear medicine were analysed, incorporating information on radiopharmaceuticals and administered activities. The method suggested by the UNSCEAR, which includes so-called essential procedures, was used for comparison. The study also investigated some frequent procedures in more detail. Results The study identifies noteworthy trends, including a threefold increase in the number of clinics offering Positron Emission Tomography (PET) procedures and a significant rise in PET usage. PET procedures constituted over 50% of the collective effective dose for adults in 2023. Despite this, Gamma Camera (GC) procedures still dominate in frequency but exhibit a steady decline. Procedures using 99mTc and 18F accounted for 93% of procedures in 2023. The collective effective dose rose 22% over the study period, with PET procedures driving this increase. PET procedures increasing role became evident by the increased contribution to the total collective dose from 15 to 52%. The UNSCEAR methodology captured 67% of the total frequency and underestimated the collective effective dose by 16%. Administered activity remained stable for the selected procedures and showed low variation between clinics. Conclusions PET procedures are increasing in scope and now constitute the largest contribution to radiation dose, and in-house production of PET radiopharmaceuticals is available in around 40% of clinics. The number of radionuclides decreased over the study period, and GC procedures declined. In general, the amount of administered activity remained stable over the period for the procedures studied. Accurately assessing utilisation and exposure trends requires extensive data, and the methodology used affects the result significantly.